Pengaruh Kepuasan Pelanggan, Kepercayaan Terhadap Loyalitas Pelanggan Pada Pempek Flamboyant - Indriyani, Yulia; Megawati, Megawati (Universitas Multi Data Palembang, 2024)
This research aims to determine the influence of customer satisfaction, product quality, brand image and trust on customer loyalty to flamboyant pempek. Respondents are customers of flamboyant pempek with a sample of 387 respondents. The results of the research are that customer satisfaction, product quality, brand image and trust have a significant positive effect on customer loyalty for pempek flamboyant